Do your ears hang low? - Cooper, Jenny, 1961- (Sterling Children's Books, an imprint of Sterling Publishing Co., 2017)
"Most kids and parents know and love the song 'Do Your Ears Hang Low?' -- and Jenny Cooper's utterly adorable illustrations will have everyone singing with joy! A little mouse leads the fun as it plays with a bloodhound's floppy, silky ears; a llama's perky, fuzzy ones; the saggy, soft ears of a lop-eared rabbit; and the flappy, happy ears of a lively piglet. A mirror at the end invites children right into the book, and entertaining 'ear' facts complete the picture!" -- Amazon.com.